Pengaruh Penerapan Prinsip Akuntansi, Ukuran Perusahaan Dan Leverage Terhadap Earnings Response Coeficient Pada Perusahaan Manufaktur Di BEI - Nulananda, Iqbal Adi; Zanaria, Yulita; Rahayu, Sri Retnaning (Expensive: Jurnal Akuntansi dan Keuangan, 2022)
This study aims to determine: (1) The effect of knowing Accounting Principles (2) The effect of knowing the effect of company size. (3) The effect of knowing the effect of Leverage on (ERC), and (4) The effect of knowing the effect of Accounting Principles, company size and Leverage together on the Earnings Response Coefficient (ERC) on Manufacturing Companies on the IDX in 2021 Sampling of 68 with the technique of collecting research data is done through purposive sampling. The research data was obtained using the EVIEWS software in 2012. The data analysis technique used analysis techniques and hypothesis testing. The results of this study indicate that: (1) Accounting Principles have a negative and insignificant effect, (2) Company size has a positive and significant effect. (3) Leverage has a negative and significant effect, and (4) Accounting Principles, Company Size, and Leverage together have an effect on Earnings Response Coeficient on Non-Financial Companies listed on the IDX